A 265-Nanometer High-Power Deep-UV Light-Emitting Diode Rapidly Inactivates SARS-CoV-2 Aerosols - Ueki, Hiroshi; Ito, Mutsumi; Furusawa, Yuri; Yamayoshi, Seiya; Inoue, Shin-ichiro; Kawaoka, Yoshihiro (mSphere, 2022)
We developed a 265-nm high-power DUV-LED irradiation system and quantitatively demonstrated that the DUV-LED can inactivate SARS-CoV-2 in suspensions and aerosols within very short irradiation times. We also found that the inactivation effect was about nine times greater against aerosolized SARS-CoV-2 than against SARS-CoV-2 suspensions. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (COVID-19) is an acute respiratory infection transmitted by droplets, aerosols, and contact. Controlling the spread of COVID-19 and developing effective decontamination options are urgent issues for the international community. Here, we report the quantitative inactivation of SARS-CoV-2 in liquid and aerosolized samples by a state-of-the-art, high-power, AlGaN-based, single-chip compact deep-UV (DUV) light-emitting diode (LED) that produces a record continuous-wave output power of 500 mW at its peak emission wavelength of 265 nm. Using this DUV-LED, we observed a greater-than-5-log reduction in infectious SARS-CoV-2 in liquid samples within very short irradiation times (<0.4 s). When we quantified the efficacy of the 265-nm DUV-LED in inactivating SARS-CoV-2, we found that DUV-LED inactivation of aerosolized SARS-CoV-2 was approximately nine times greater than that of SARS-CoV-2 suspension. Our data demonstrate that this newly developed, compact, high-power 265-nm DUV-LED irradiation system with remarkably high inactivation efficiency for aerosolized SARS-CoV-2 could be an effective and practical tool for controlling SARS-CoV-2 spread. IMPORTANCE We developed a 265-nm high-power DUV-LED irradiation system and quantitatively demonstrated that the DUV-LED can inactivate SARS-CoV-2 in suspensions and aerosols within very short irradiation times. We also found that the inactivation effect was about nine times greater against aerosolized SARS-CoV-2 than against SARS-CoV-2 suspensions. The DUV-LED has several advantages over conventional LEDs and mercury lamps, including high power, compactness, and environmental friendliness; its rapid inactivation of aerosolized SARS-CoV-2 opens up new possibilities for the practical application of DUV-LEDs in high-efficiency air purification systems to control airborne transmission of SARS-CoV-2.